Surviving State Terror : Women's Testimonies of Repression and Resistance in Argentina - Sutton, Barbara, 1970- (Book collections on Project MUSE., 2018)
Honorable Mention, 2019 Distinguished Book Award, given by the Sex & Gender Section of the American Sociological Association Honorable Mention, 2019 Marysa Navarro Book Prize, given by the New England Council of Latin American Studies (NECLAS)A profound reflection on state violence and women's survivalIn the 1970s and early 80s, military and security forces in Argentina hunted down, tortured, imprisoned, and in many cases, murdered political activists, student organizers, labor unionists, leftist guerrillas, and other people branded "subversives." This period was characterized by massive human rights violations, including forced disappearances committed in the name of national security. State terror left a deep scar on contemporary Argentina, but for many survivors and even the nation itself, talking about this dark period in recent history has been difficult, and at times taboo. For women who endured countless forms of physical, sexual, and emotional violence in clandestine detention centers, the impetus to keep quiet about certain aspects of captivity has been particularly strong. In Surviving State Terror, Barbara Sutton draws upon a wealth of oral testimonies to place women's bodies and voices at the center of the analysis of state terror. The book showcases poignant stories of women's survival and resistance, disinterring accounts that have yet to be fully heard, grappled with, and understood. With a focus on the body as a key theme, Sutton explores various instances of violence toward women, such as sexual abuse and torture at the hands of state officials. Yet she also uses these narratives to explore why some types of social suffering and certain women's voices are heard more than others, and how this can be rectified in our own practices of understanding and witnessing trauma. In doing so, Sutton urges us to pay heed to women survivors' political voices, activist experiences, and visions for social change. Recounting not only women's traumatic experiences, but also emphasizing their historical and political agency, Surviving State Terror is a profound reflection on state violence, social suffering, and human resilience--both personal and collective